(untitled) (International Journal of Artificial Intelligence, Computer Science, Management and Technology, 2025)
The integration of the Internet of Things (IoT) and Artificial Intelligence (AI) has revolutionized warehouse management by enabling real-time inventory tracking, predictive analytics, and enhanced automation. This research paper explores the transformative impact of IoT and AI in modern warehousing, highlighting technological advancements, operational benefits, and challenges. By examining case studies of leading organizations, this paper illustrates the role of smart warehousing in optimizing logistics, reducing costs, and improving overall supply chain efficiency. The findings underscore the necessity for businesses to adopt these technologies for sustainable growth in an increasingly digital economy.